Evaluating glymphatic pathway function utilizing clinically relevant intrathecal infusion of CSF tracer - Yang, Lijun (BioMed Central, 2013)
BACKGROUND: Neurodegenerative diseases such as Alzheimer’s are associated with the aggregation of endogenous peptides and proteins that contribute to neuronal dysfunction and loss. The glymphatic system, a brain-wide perivascular pathway along which cerebrospinal fluid (CSF) and interstitial fluid (ISF) rapidly exchange, has recently been identified as a key contributor to the clearance of interstitial solutes from the brain, including amyloid β. These findings suggest that measuring changes in glymphatic pathway function may be an important prognostic for evaluating neurodegenerative disease susceptibility or progression. However, no clinically acceptable approach to evaluate glymphatic pathway function in humans has yet been developed. METHODS: Time-sequenced ex vivo fluorescence imaging of coronal rat and mouse brain slices was performed at 30–180 min following intrathecal infusion of CSF tracer (Texas Red- dextran-3, MW 3 kD; FITC- dextran-500, MW 500 kD) into the cisterna magna or lumbar spine. Tracer influx into different brain regions (cortex, white matter, subcortical structures, and hippocampus) in rat was quantified to map the movement of CSF tracer following infusion along both routes, and to determine whether glymphatic pathway function could be evaluated after lumbar intrathecal infusion. RESULTS: Following lumbar intrathecal infusions, small molecular weight TR-d3 entered the brain along perivascular pathways and exchanged broadly with the brain ISF, consistent with the initial characterization of the glymphatic pathway in mice. Large molecular weight FITC-d500 remained confined to the perivascular spaces. Lumbar intrathecal infusions exhibited a reduced and delayed peak parenchymal fluorescence intensity compared to intracisternal infusions. CONCLUSION: Lumbar intrathecal contrast delivery is a clinically useful approach that could be used in conjunction with dynamic contrast enhanced MRI nuclear imaging to assess glymphatic pathway function in humans.